Improving The Role Of Family In Preventing Anemia In Adolescent Girls Through Health Education: A Systematic Literature Review - Dedah Ningrum; Endrixs Endrianto; Winarto; Andi Lala (PT. Anagata Sembagi Education, 2025)
Anemia in adolescent girls is a significant global health problem, with a high prevalence in developing countries, including Indonesia, and can adversely affect physical, mental health, and academic performance. This study aims to analyze the role of families in preventing anemia in adolescent girls through health education and evaluate the effectiveness of family-based interventions. The method used was a systematic literature review by collecting data from various relevant scientific articles published in the last 10 years. The results showed that family involvement, especially mothers, in educating about the importance of consuming iron-rich foods and monitoring iron supplements proved effective in reducing the prevalence of anemia in adolescent girls. Intervention programs that involve families in nutrition education also show increased awareness and changes in healthier eating habits. However, challenges such as economic limitations, culture, and parents' education level are still barriers that need to be overcome. The implication of this study is the need to develop more comprehensive and family-based anemia prevention programs, as well as policies that support access to nutritious foods and iron supplements. Collaboration between the health, education and government sectors is essential to create a supportive environment for sustainable anemia prevention efforts.